The Dynamics of Complex Urban Systems An Interdisciplinary Approach - Albeverio, Sergio; Andrey, Denise; Giordano, Paolo; Vancheri, Alberto (Physica-Verlag HD : Imprint: Physica, 2008)
The present book outlines a conceptual framework for modelling and forecasting the dynamics of both growth-limited cities and megacities bringing together experts from several disciplines. The interdisciplinary point of view is particularly stressed. The contributions presented reflect the various interdependencies between structural (physics and mathematics models) and social development (spatial decision making and urban planning models). The volume emphasizes not only the contributions from different disciplines but also pays attention to specific problems like model calibration, data availability and management, case studies and interactions with urban planners. It is the collection of all the contributions of the speakers at the international workshop "The Dynamics of Complex Urban Systems: an interdisciplinary approach" held at Monte Verità (Ascona/Switzerland) from 4th to 6th of November 2004.